2018
DOI: 10.1186/s13750-018-0129-z
|View full text |Cite
|
Sign up to set email alerts
|

How does roadside vegetation management affect the diversity of vascular plants and invertebrates? A systematic review

Abstract: Background: With appropriate management, based on vegetation removal that reverses late-successional vegetation stages, roadsides can support high levels of biodiversity. However, current recommendations for roadside management to conserve or restore biodiversity are largely based on research on non-roadside grassland habitats, and much of the evidence on how roadside management practices affect biodiversity is found in non-peer-reviewed grey literature. Therefore, based on suggestions from key stakeholders an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 35 publications
0
60
0
4
Order By: Relevance
“…Existing studies suggest that removing verge cuttings benefits plant and insect diversity (Jakobsson et al, 2018), and flower abundance (Noordijk et al, 2009 Another limitation of our findings of the impacts of verge cutting is that the weather in the study year was particularly hot and dry, which may have accentuated the slow recovery of plant and flower communities. Our findings suggest that multiple cuts would be detrimental to flower production in drought years, at least if cuttings were not removed.…”
Section: Modelmentioning
confidence: 85%
See 1 more Smart Citation
“…Existing studies suggest that removing verge cuttings benefits plant and insect diversity (Jakobsson et al, 2018), and flower abundance (Noordijk et al, 2009 Another limitation of our findings of the impacts of verge cutting is that the weather in the study year was particularly hot and dry, which may have accentuated the slow recovery of plant and flower communities. Our findings suggest that multiple cuts would be detrimental to flower production in drought years, at least if cuttings were not removed.…”
Section: Modelmentioning
confidence: 85%
“…Road verge management affects their conservation value, though research has mostly focused on plants (Jakobsson, Bernes, Bullock, Verheyen, & Lindborg, 2018). A plot experiment along a single road verge found that cutting twice a year resulted in more flowers and insects than cutting once or no management (Noordijk, Delille, Schaffers, & Sýkora, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Piepenschneider, Bühle, Hensgen, & Wachendorf, ; Appendix ), which are often a by‐product of routine road verge management. The diversity of plants and insects benefits from cuttings being removed from road verges, which reduces soil nutrients and provides gaps for seedlings (Jakobsson et al, ). Currently, cuttings are rarely removed due to the financial costs of collection and disposal but using cuttings for biogas might make their removal financially viable and even profitable.…”
Section: Management For Esmentioning
confidence: 99%
“…However, both the financial and environmental costs of management must be considered. For example, management frequency and the machinery required will affect the amount of noise pollution and fossil fuel emissions, and therefore the net benefits of the ES provided (Säumel et al, 2016), though also the demand for mitigating ES Mowing twice per year and removing hay is optimal for plant diversity (reviewed in Jakobsson et al, 2018) and insect pollinators (Noordijk et al, 2009) Leaving areas uncut reduces water flow and improves water filtration (Henderson et al, 2016) (Continues) species richness (reviewed in Jakobsson, Bernes, Bullock, Verheyen, & Lindborg, 2018), flower species richness, flower abundance and pollinator abundance (Noordijk, Delille, Schaffers, & Sýkora, 2009), which are likely to benefit pollination services and a range of other ES (Schwarz et al, 2017).…”
Section: Routine Managementmentioning
confidence: 99%
“…For example, the data do not indicate whether clippings were left on-site or removed. While we observed mulched clippings in some recently-mowed vacant lots, we were unable to examine the effects of this practice, which other studies have found to be important in nitrogen cycling and plant community dynamics (Maron & Jeffries, 2001;Kopp & Guillard, 2002;Schippers & Joenje, 2002;Qian et al, 2003;Jakobsson et al, 2018). Furthermore, an examination of urban soils and the characteristics shaping the below-ground biotic and abiotic profiles of the area is necessary to truly understand the drivers of plant diversity in vacant lots.…”
Section: F I G U R Ementioning
confidence: 89%